2004
DOI: 10.1097/00004032-200404000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Patient Size and X-Ray Transmission in Body Ct

Abstract: Physical characteristics were obtained for 196 patients undergoing chest and abdomen computed tomography (CT) examinations. Computed tomography sections for these patients having no evident pathology were analyzed to determine patient dimensions (AP and lateral), together with the average attenuation coefficient. Patient weights ranged from approximately 3 kg to about 120 kg. For chest CT, the mean Hounsfield unit (HU) fell from about -120 HU for newborns to about -300 HU for adults. For abdominal CT, the mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Many metrics of patient size, including weight (15,31), body mass index (32), cross-sectional diameter (33), and perimeter (13), have been used previously for CT dosimetry calculations. The D eff , as selected by the AAPM, is a reasonable choice for manual measure, but it has limitations in regions of irregular body contours that used by each manufacturer (27,29).…”
Section: Medical Physics: Estimating Patient Dose From X-ray Tube Outmentioning
confidence: 99%
“…Many metrics of patient size, including weight (15,31), body mass index (32), cross-sectional diameter (33), and perimeter (13), have been used previously for CT dosimetry calculations. The D eff , as selected by the AAPM, is a reasonable choice for manual measure, but it has limitations in regions of irregular body contours that used by each manufacturer (27,29).…”
Section: Medical Physics: Estimating Patient Dose From X-ray Tube Outmentioning
confidence: 99%
“…17,18 For larger patients typically encountered in chest CT, however, the x-ray tube voltage may need to be increased to ensure that there is adequate patient penetration by the x-ray beam. 19 Accordingly, it is important that methods for dosimetry in CT imaging are equipped to deal with the complete range of x-ray tube voltages ͑i.e., 80 to 140 kV͒ that current scanners offer.…”
mentioning
confidence: 99%
“…It was shown that, although it is common practice to adapt tube load to patient age and size, [9][10][11][26][27][28][29][30][31] …”
Section: Discussionmentioning
confidence: 99%